1998
DOI: 10.1073/pnas.95.11.6526
|View full text |Cite
|
Sign up to set email alerts
|

Water does not flow across the tight junctions of MDCK cell epithelium

Abstract: Although it has been known for decades that the tight junctions of f luid-transporting epithelia are leaky to ions, it has not been possible to determine directly whether significant transjunctional water movement also occurs. An optical microscopic technique was developed for the direct visualization of the f low velocity profiles within the lateral intercellular spaces of a f luid-absorptive, cultured renal epi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 13 publications
4
42
0
Order By: Relevance
“…Since the discovery of aquaporin (AQP) water channels in both epithelial cell membranes, the molecular basis of a transcellular pathway has been evident . By contrast, the contribution of the paracellular pathway through the tight junctions (TJ) was estimated to be between 0 and 100%, depending on the method used for analysis (Kovbasnjuk et al, 1998;Quigley and Baum, 2002;Shachar-Hill and Hill, 2002;Spring, 1998;Zeuthen, 1995). Although TJs are often named aqueous pores, there is, as yet, no direct experimental evidence of paracellular water flux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of aquaporin (AQP) water channels in both epithelial cell membranes, the molecular basis of a transcellular pathway has been evident . By contrast, the contribution of the paracellular pathway through the tight junctions (TJ) was estimated to be between 0 and 100%, depending on the method used for analysis (Kovbasnjuk et al, 1998;Quigley and Baum, 2002;Shachar-Hill and Hill, 2002;Spring, 1998;Zeuthen, 1995). Although TJs are often named aqueous pores, there is, as yet, no direct experimental evidence of paracellular water flux.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from analytical calculations (Weinstein and Stephenson, 1981a;Weinstein and Stephenson, 1981b), two experimental approaches have been reported: the fluidphase fluorescent tracer technique in combination with confocal microscopy (Segawa et al, 2002) and optical methods for visualizing fluid movement in the lateral intercellular space (Kovbasnjuk et al, 1998). These investigations yielded, in part, contrasting results.…”
Section: Introductionmentioning
confidence: 99%
“…1 describes water flow via a transcellular pathway as found by Rivers et al (1996) who studied populations of MDCK cysts. This was also found to be the case by Kovbasnjuk et al (1998) who developed an optical microscopic technique to visualize the flow velocity profiles within the lateral intercellular spaces and to test for fluid flow across the tight junction. The flow velocity within the lateral intercellular spaces fell almost to zero adjacent to the tight junction, indicating that transjunctional flow can be neglected.…”
mentioning
confidence: 96%
“…However, there is a precedent for a completely transcellular flow of water in an electrically 'leaky' epithelium. Using a direct visualization technique, Kovbasnjuk and colleagues reported that water did not flow through the paracellular pathway in an MDCK (renal) cell epithelium, even when osmotic gradients were applied (Kovbasnjuk et al, 1998). However, the situation in the killifish gut appears to be very different from that in the mammalian gut where much of the increased intestinal water absorption accompanying a meal appears to be paracellular, and serves to drive the paracellular absorption of ions and nutrients by convective solvent drag, at minimal metabolic cost (Pappenheimer and Reiss, 1987;Madara and Pappenheimer, 1987).…”
Section: Differences Between Euryhaline Fish and Mammalsmentioning
confidence: 99%